Radiographic Assessment of the Quality of Post and Core Restorations and the Effect of the Gap Between the Post-Restoration and the Remaining Root Canal Filling on the Apical Status in a Saudi Subpopulation - Almohefer,Sami; Alkattan,Rana; Alshubrami,Ruqayyah; Alshammari,Fajr; Alnaseeb,Nawal; Tamim,Hani; Madfa,Ahmed (Clinical, Cosmetic and Investigational Dentistry, 2025)
Sami A Almohefer,1 Rana Alkattan,2– 4 Ruqayyah H Alshubrami,5 Fajr Y Alshammari,5 Nawal M Alnaseeb,5 Hani Tamim,6 Ahmed A Madfa1 1Department of Restorative Dental Science, College of Dentistry, University of Ha’il, Ha’il, Kingdom of Saudi Arabia; 2Department of Restorative and Prosthetic Dental Sciences, College of Dentistry, King Saud Bin Abdulaziz University for Health Sciences (KSAU-HS), Riyadh, Kingdom of Saudi Arabia; 3King Abdullah International Medical Research Center, Ministry of National Guard Health Affairs, Riyadh, Kingdom of Saudi Arabia; 4Dental Services King Abdulaziz Medical City, Ministry of the National Guard- Health Affairs, Riyadh, Kingdom of Saudi Arabia; 5College of Dentistry, University of Ha’il, Ha’il, Kingdom of Saudi Arabia; 6Department of Epidemiology and Biostatistics, College of Medicine, Alfaisal University, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Sami A Almohefer, Department of Restorative Dental Science, College of Dentistry, University of Hail, Hail, Kingdom of Saudi Arabia, Tel +966165358200, Email S.almohefer@uoh.edu.saBackground: The objective of this study was to assess the quality of post and core restorations carried out by general dentists in the Hail region of Saudi Arabia using periapical radiographs. Additionally, the assessment included the examination of periapical lesions.Methods: A comprehensive analysis was conducted on 301 periapical digital radiographs to assess various factors including the type of post, type of coronal restoration, post length in relation to crown and root length, presence of any abnormalities in the post space, condition of the remaining gutta-percha (GP), gap between the end of the post and the GP, and the presence of apical lesions. Analysis was conducted to determine the frequency distribution and cross-tabulation of the variables.Results: Prefabricated metallic posts were most commonly used (62.1%), followed by metal posts which were found in 28.9% of the cases, and fiber posts which were used in 9.0% of the cases. The ...